2018
DOI: 10.1016/j.foodres.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Edible flowers as sources of phenolic compounds with bioactive potential

Abstract: A B S T R A C TThe edible flowers are widely used, but there is still a lot to be done in relation to its bioactive potential and its correlation with the presence of phenolic compounds. The aim of this study was determined the individual phenolic profile in the hydromethanolic extracts and infusion preparations of four different flower samples (Dahlia mignon, Rosa damascena 'Alexandria' and R. gallica 'Francesa' draft in R. canina, Calendula officinalis L., and Centaurea cyanus L.) and their bioactive potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
143
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 38 publications
(41 reference statements)
10
143
1
9
Order By: Relevance
“…Treatment with UE extracts, in concentrations between 0.02 and 0.32 µg GAE/mL, has not induce any significant decrease in cells viability compared to non-treated cells, as shown in Figure 4. Our results appear to be well supported by previous investigations that report a hardly any or no cytotoxicity and antiproliferative effect of Centaurea extracts at low dose against human cell lines, e.g., NALM-6, REH, NB4, KMM-1 [42], HepG2 [43], Caco-2 [44], and A549 [19].…”
Section: In Vitro Bioactive Antioxidant Assayssupporting
confidence: 92%
“…Treatment with UE extracts, in concentrations between 0.02 and 0.32 µg GAE/mL, has not induce any significant decrease in cells viability compared to non-treated cells, as shown in Figure 4. Our results appear to be well supported by previous investigations that report a hardly any or no cytotoxicity and antiproliferative effect of Centaurea extracts at low dose against human cell lines, e.g., NALM-6, REH, NB4, KMM-1 [42], HepG2 [43], Caco-2 [44], and A549 [19].…”
Section: In Vitro Bioactive Antioxidant Assayssupporting
confidence: 92%
“…A peak was observed in F2 petals with a subsequent decrease up to F5 (Figure 2E). Different studies reported that bioactivity of edible flowers is highly correlated to bioactive compounds especially to phenolic compounds composition [48][49][50][51]. Significant differences in both phenolic compounds and antioxidant activity between edible flowers have been found [49].…”
Section: Bioactive Compounds and Antioxidant Activitymentioning
confidence: 99%
“…In the food area, there are trends related to the vegan food movement and the potentialities of edible flowers (like dahlia and rose) as a source of phenolic compounds, with bioactive potential that can be incorporated in human diet [9], [10]. The antioxidant activity of the edible flowers can be very high, when compared to conventional vegetables and fruits used in human diet (from 3.6 for Calendula officinalis to 70.4 for Tagetes erecta) [11].…”
Section: A the Importance Of The Production Of Edible Plants In Greementioning
confidence: 99%